Economic policy uncertainty spillovers in small open economies: The case of Hong Kong. (12th September 2018) - Luk, Paul; Cheng, Michael; Ng, Philip; Wong, Ken
Abstract: This paper studies the extent to which economic policy uncertainty shocks in major economies affect real economic activity in small open economies. We use Hong Kong as a case study. Following Baker, Bloom and Davis (2016), we construct a newspaper‐based economic policy uncertainty index for Hong Kong for the period 1998 to 2016. We estimate international spillovers of uncertainty and find large spillovers of uncertainty from major economies to Hong Kong. Furthermore, using a structural vector autoregressive approach, we show that a rise in domestic economic policy uncertainty leads to tight financial conditions, and lower investment and vacancy posting, dampening domestic output growth.